Factors that influence perception of seriousness of crime : The application of race, type of offence and dispositional empathy to an Australian context - Larkins, Giselle (2008)
The perception of seriousness of crime may be altered by numerous extra-legal factors within the criminal justice system. It is of significant importance to understand the ways in which various factors contribute to the differential treatment of defendants. Prejudicial attitudes towards Indigenous people pervade all areas of Australian society, including the criminal justice system (Paradies, 2005). For instance, although Indigenous people form approximately 2.4% of the general Australian population, they contribute to 24% of the total prison population (ABS, 2007; Paradies). Despite this, few studies have actively sought to better understand the factors that may contribute to varied perceptions of crimes committed by either Caucasian or Indigenous Australians. The aim of this review was to thus consider the effect of race of the defendant and type of crime committed upon offence perception. Furthermore, the psychological variable of dispositional empathy was reviewed in its application to the judgement of crime. The review found that there was a dire lack of research evident concerning the effect of factors upon the perceptions of crimes committed by Caucasian and Indigenous Australians. The studies conducted upon the effect of race in Australia have been inconclusive and contradictory. Furthermore, the effect of type of crime has not been actively explored within Australian studies, with only certain crimes, such as interpersonal and property offences, being applied to research. Finally, research into the effect of dispositional empathy on perceptions of crime is virtually non-existent. The area of perceptions of seriousness of crime thus requires significantly more research within an Australian context. It can be hoped that, from such research, the disadvantage of Indigenous Australians and also Caucasian Australians, within the justice system can be finally overcome. Indigenous Australians suffer disadvantage at all levels of Australian society. This is especially so within the criminal justice system, in which Indigenous Australians are chronically over-represented. However, little research has assessed the extra-legal factors that may contribute to the differential perception of and consequent disparity in sentencing of crimes committed by Indigenous and Caucasian Australian offenders. This study (n = 101) examined the effect of the three variables of type of crime committed, race of the offender, and dispositional empathy upon the perception of crime seriousness and consequent punishment of offences committed by either an Indigenous or Caucasian offender. It was hypothesised that assault would be perceived as more serious and thus more harshly punished than fraud. Furthermore, that crimes committed by Indigenous offenders would be perceived as more serious and thus more harshly punished. It was considered that racial disparity in perception of crime would be especially emphasised in crimes that were stereotypically consistent with an offenders race. Lastly, it was hypothesised that participants who shared racial similarity with an offender would thus have higher dispositional empathy towards them and consequently perceive the crime as less serious and punish less severely. Consistent with previous research, the type of crime committed was found to slightly impact the perceived severity of crime. Race of the offender was not found to effect perceptions of crime seriousness or punishment, which may have been due to a watchdog effect of modern racism or low prejudice rates amongst participants. Lastly, dispositional empathy did not have an impact on perceptions of crime seriousness and punishment in the present study. However, further research upon the impact of extra-legal variables within the Australian justice system is required, so that the over-representation of racial minority groups might be better understood